Hydrogen production by immobilized Synechocystis sp. PCC 6803 - Touloupakis, Eleftherios (2016)
The ability of the immobilized Synechocystis sp. PCC 6803 cells to produce hydrogen via an indirect light driven process was investigated. Cells were successfully immobilized in a calcium alginate gel matrix. Beads were prepared by using 3% (w/v) alginate and 2% (w/v) calcium chloride, and were stable showing minimal cell leakage. Beads had a mean diameter of 5.06 ± 0.18 mm, a volume of 67.8 ± 2.4 μL and a mean cell dry weight of 46.3 ± 0.8 μg. Immobilized cells retained their viability, as shown by measurement of the Fv/Fm ratio, for at least 30 days. The maximum rate of hydrogen production reached 5.73 ± 0.69 mL H2 mg cells−1 (e.g., 40.6 ± 4.9 μmol H2 mg chl−1 h−1).